Forage growth, biomass yield and nutrient content of two different hybrid Napier cultivars grown in Bangladesh (Bangladesh Journal of Animal Science, 2021)
A 2×3 factorial experiment was conducted to compare two cultivars; Bangladesh Livestock Research Institute developed Napier hybrid-3 (BN-3) (Pennisetum purpureum) and Pakchong-1 (Pennisetum purpureum× P. glaucum) in terms of forage growth, biomass yield, and nutritional quality. Cultivars were cultivated in 03 blocks with 03 replicates and were harvested at 03 cutting periods (40, 50, and 60 days). Plot sizes for each cultivar were 25 m2 (5m × 5m), and in every plot, twenty-five stem cuttings with two healthy nodes per cutting were planted with (1×1) m spacing. The effects of cultivar and cutting period were significant on plant height, leaves per tiller, leaf DM production, and leaf stem ratio (LSR). Highest plant height (P